MTA1‐activated Epi‐microRNA‐22 regulates E‐cadherin and prostate cancer invasiveness. Issue 6 (12th March 2017) - Dhar, Swati; Kumar, Avinash; Gomez, Christian R.; Akhtar, Israh; Hancock, John C.; Lage, Janice M.; Pound, Charles R.; Levenson, Anait S.
Abstract : We have previously shown that metastasis‐associated protein 1 (MTA1), a chromatin remodeler, plays an important role in prostate cancer invasiveness, likely through regulation of epithelial‐to‐mesenchymal transition. Here, we identified miR‐22 as an epigenetic‐microRNA (Epi‐miR) directly induced by MTA1 and predicted to target E‐cadherin. Loss‐of‐function and overexpression studies of MTA1 reinforced its regulatory role in miR‐22 expression. MiR‐22 directly targets the 3′‐untranslated region of E‐cadherin, and ectopic overexpression of miR‐22 diminishes E‐cadherin expression. Overexpression of miR‐22 in prostate cancer cells promotes cell invasiveness and migration. Meta‐analysis of patient tumor samples indicates a positive correlation between MTA1 and miR‐22, supporting their inhibitory effect on E‐cadherin expression. Our findings implicate the MTA1/Epi‐miR‐22/E‐cadherin axis as a new epigenetic signaling pathway that promotes tumor invasion in prostate cancer. Abstract :